New Geographies of Work: Re-Scaling Micro-Worlds - Hans-Joachim Bürkner; Bastian Lange (European Spatial Research and Policy, 2020)
The recently emerging new types of collaborative work and unconventional workplaces indicate that shifting social and economic practices have odd spatial implications. The diversity of work, mostly based on hybrid social and economic logics, has brought forth a~number of new contextualised spatial constructs in recent years: makerspaces, fab labs, open workshops, and co-working spaces now require detailed analytical reconstruction and conceptualisation. This article is a~theoretical discussion of the nature of fluid and contingent spatialisation against the backdrop of binary explanatory categories (e.g. local-global; proximity-distance). Drawing upon modernised concepts of horizontal scaling, we propose a~perspective on hybrid work which focuses on contingent multiple, multidirectional and temporal scalings created by a~variety of users while developing their own micro-worlds of work.
Keywords: 710; scale; flat ontology; new work; alternative workplaces; collaboration; social innovation